Pengaruh Persepsi Kualitas Pelayanan, Pemahaman, Persepsi Sanksi Perpajakan, dan Lingkungan Terhadap Kepatuhan Wajib Pajak - Noviantari, Putri; Setiawan, Putu Ery (E-Jurnal Akuntansi, 2018)
Taxpayer compliance is important because most of state revenues come from tax revenues. Taxpayer compliance is the taxpayer's obedience to perform the required provisions or tax rules. Taxpayer compliance becomes a requirement for increased state revenues. Taxpayer compliance is an important factor because the system implements in taxation system Indonesia is self assessment system. The low compliance of taxpayers can lead to reduced receipts to the state treasury and hindering the running of government wheels because most of state expenditures are financed by tax revenues. This study focuses on taxpayer compliance non taxable entrepreneurs in Pratama Badung Selatan tax office. The purpose of this research is to know the influence of perception of service quality, understanding of taxpayer, perception of tax sanction, and environment of taxpayer on taxpayer compliance non taxable entrepreneur in Pratama Badung Selatan tax office. The number of samples used is as much as 100 respondents and determined by the slovin formula. Sample determination was done by incidental sampling method. Data collection was done by distributing questionnaires to respondents. Data analysis technique used is multiple linear regression. Based on the results of the analysis found that the perception of service quality, understanding of taxpayers, perceptions of tax sanctions, and environmental taxpayers have a positive and significant impact on taxpayer compliance. Keywords: Compliance, perception of service quality, understanding, perception of tax sanction, environment